LogiQL: A Query Language for Smart Databases (ProtoView, 2015)
For readers with at least a basic background in computer programming, Halin and Rugaber introduce programming in LogiQL, a declarative logic programming language developed to harness the power of first-order logic to support access to databases, influenced by Prolog and Datalog.